Pendekatan Teori Health Belief Model terhadap Perilaku Ibu dalam Pemenuhan Kebutuhan Nutrisi Anak Usia Toddler - Rambu Eri Hupunau; Retnayu Pradanie; Tiyas Kusumaninggrum (Universitas Airlangga, 2019)
Introduction: Toddler is an important period in child growth that will determine the development of children in the future. If nutritional needs are not met properly during infancy, it will lead to malnutrition of children who are susceptible to infection, muscle management, swelling of the liver, and organ abnormalities and functions (due to atrophy). The purpose of this study is to explain the factors that influence the mother in providing nutritional needs of toddlers with the health belief model approach.Methods: This study design was descriptive with cross sectional approach. Total sampel in this study was 174 mothers respondents who has child with age 1–3 years. Independent variabel in this study were perceived suceptibility, perceived severity, perceived benefit, perceived barrier, cues to action and self eficacy. Dependent variabel study was Mother's behavior in providing nutrition. Sampel were taken by Cluster random sampling. The data were collected by questionnaire. Data were analyzed with spearmen rho test with significance level α< 0.05.Results: The result showed that perceived suceptibility (p=0.382), perceived severity (p=0.116), perceived benefit (p=0.182), cues to action (p=0.075) and self eficacy (p=0.132) theres was no relationship between mother’s behavior and perceived barrier (p=0.033) have relationship with mother’s behavior.Conclusion: Health workers in Puskesmas should do intensive health education about good nutrition and the consequences that can occur if lack of nutrition in toddler children. Then for mothers as respondents to empower local food available to be a source of nutritional substitutes and use the home page to become a family garden by planting various types of vegetables.